Imagens de França do século XVIII através da colecção cartográfica do Visconde de Balsemão - Coutinho, Ana Sofia de Almeida (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The Public Municipal Library of Porto preserves a collection of cartographical representations of France dating from the 18th century. An inventory of this collection that once belonged to the Viscount of Balsemão, was carried out in 2002. By identifying the technical and historical aspects of this cartographical collection and making its geographical reading, the objective was twofold: to disclose the image of the French territory given through these maps and atlases, and to perceive the purpose of their purchasing at that time.